Orthokeratology-Associated Infectious Keratitis in a Tertiary Care Eye Hospital in Hong Kong - Chan, Tommy C.Y.; Li, Emmy Y.M.; Wong, Victoria W.Y.; Jhanji, Vishal (American journal of ophthalmology, 2014)
To analyze cases of orthokeratology-associated infectious keratitis managed in a tertiary care eye hospital in Hong Kong between 2003 and 2013. Retrospective study. Case records of patients with infectious keratitis attributable to orthokeratology contact lenses were analyzed. Data analyzed included clinical features, microbiological evaluation, and treatment outcomes. A total of 23 patients were included (16 female, 7 male, mean age: 15.0 ± 4.2 years; range: 9–23 years). All patients were using overnight orthokeratology for an average of 2.7 ± 2.8 years (range: 3 months - 10 years) before the onset of infection. Clinical features included corneal infiltrate (n = 14, 60.9%) and corneal perineuritis (n = 12, 52.2%). Fifteen eyes (65.2%) had a positive microbiological culture obtained from corneal scrapings. The most commonly isolated organism was Pseudomonas aeruginosa (n = 6), followed by coagulase-negative Staphylococcus (n = 5) and Acanthamoeba (n = 3). Five cases of Pseudomonas aeruginosa and 5 cases of Acanthamoeba were identified from contact lenses or contact lens solution. The mean duration from disease onset to remission was 31.9 ± 34.9 days (range: 6–131 days). All patients responded to medical treatment, and no emergency surgical intervention was needed. The best-corrected logMAR visual acuity improved significantly from 0.62 ± 0.51 (20/83 Snellen) to 0.15 ± 0.20 (20/28 Snellen) (Wilcoxon signed rank test, P < .001). Orthokeratology-associated infectious keratitis continues to be a serious problem, especially in regions with high prevalence of myopia. Early clinical and microbiological diagnosis and intensive treatment can improve final visual outcomes.